Frailty is associated with chronic inflammation and pro-inflammatory monocyte subpopulations. (25th November 2020) - Cybularz, M; Wydra, S; Berndt, K; Poitz, D; Barthel, P; Pfluecke, C; Linke, A
Abstract: Introduction: Patients with frailty represent an increasing patient group in the intensive care medicine. A connection between frailty and inflammation has been suggested. An increased mortality rate in patients with high grade aortic valve stenosis (AS) and frailty, who underwent Transcatheter Aortic Valve Implantation (TAVI) has been observed. A systemic inflammatory reaction in the intensive care unit in the first days after TAVI is a positive predictive factor for an unfavorable outcome. Exact mechanisms are still not fully explained. Monocyte subpopulations are associated with both cardiovascular diseases and a high APACHE II score in critically ill patients. Purpose: This study investigates the correlation between frailty and cellular and systemic inflammatory mechanisms and mortality after TAVI. Methods: We examined 120 patients with symptomatic AS who underwent TAVI. Before the implantation, frailty status has been assessed. In all patients a flow cytometry analysis has been performed. Monocyte subpopulations were defined as follows: Mon1 (CD14++CD16–), Mon2 (CD14++CD16+) and Mon3 (CD14+CD16++). Expression of CD11b has been measured as a marker for monocyte activation. Pro-inflammatory cytokines such as interleukin IL-8, as well as CRP have been measured with Cytometric Bead Array or standard laboratory methods. Results: After 3 months 15 of 120 patients died, primarily without relevant dysfunction of the implanted aortic valve. In 8 of 15 (53%) of the deceased patients and 20 of 100 (19%) of the surviving patients, frailty could be diagnozed before TAVI (p=0.003). Patients with frailty showed prior to TAVI signs of chronic inflammation: elevated CRP (3.7 vs. 5.9 mg/l, p=0.001) and elevated levels of considered as pro-inflammatory Mon2 monocytes (37 vs. 53, p=0.001). Expression of CD11b and IL-8 showed an increasing trend in patients with frailty. Frailty, the monocyte markers, IL-8 and CRP prior to TAVI correlated with increased early mortality after TAVI. Conclusion: A considerable number of elderly patients with high grade aortic valve stenosis can be described as frail. This syndrome is associated with increased mortality and with signs of chronic systemic inflammation and pro-inflammatory monocytes. Funding Acknowledgement: Type of funding source: Private hospital(s). Main funding source(s): Heart Center Dresden